2017
DOI: 10.3390/app7040310
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Unsteady Flow Characteristics of a SCO2 Centrifugal Compressor

Abstract: Supercritical carbon dioxide (SCO 2 ) is a vital working fluid in the application of power units and its high density helps to achieve a compact mechanical structure. Centrifugal compressors are of vital use in various kinds of equipment. In this paper, a SCO 2 centrifugal compressor of large input power and mass flow rate is designed and numerically investigated. A thorough numerical analysis of the unsteady flow field in the centrifugal compressor is performed in ANSYS-CFX. The computation adopts hexahedral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Therefore, the RNG k-ε was used for calculation. The model was developed by Yokhot and Orszag et al [27,28] using the RNG method based on the standard k-ε model, which is suitable for the simulation of high-speed gas flow [7,14,[29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the RNG k-ε was used for calculation. The model was developed by Yokhot and Orszag et al [27,28] using the RNG method based on the standard k-ε model, which is suitable for the simulation of high-speed gas flow [7,14,[29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…Centrifugal compressors are a class of machinery universally used in industry [1] that have a wide range of applications and consume a large amount of energy. The demands of industry, resulting from the need to sustain and accelerate economic growth, have meant that multistage centrifugal compressors are widely used.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the inlet condition was approaching the critical point, their deviation became more and more obvious. Yuqi Wang et al (2017) carried out steady and unsteady numerical simulations of a SCO 2 centrifugal compressor with ANSYS-CFX [19], which showed that the difference between the two results is small. But, it should be pointed out that the equation of state used in their calculation is not accurate enough for SCO 2 .…”
Section: Introductionmentioning
confidence: 99%